Peningkatan Kapasitas Pengelola Desa Wisata melalui Pelatihan Manajemen dan Promosi Digital Berbasis Potensi Lokal - Muh. Hamzah; Fatimah Nur’aini; Umi Masruro (Yayasan Literasi Altruis Khatulistiwa, 2026)
This community service program aims to enhance the capacity of tourism village managers through training in tourism management and digital promotion based on local potential in Gading Wetan Village, Probolinggo Regency. The program was implemented using a Participatory Action Research (PAR) approach, involving 32 participants consisting of village officials, tourism awareness groups (Pokdarwis), youth organizations, and local micro, small, and medium enterprises (MSMEs). Activities included needs assessment, tourism management training, digital promotion training, and assistance in creating promotional content. The results of this program showed a significant increase in participants' understanding and skills, reflected in the average pre-test score improvement from 42% to 81%. Participants are now able to manage digital media and independently produce promotional content, such as photos, videos, and destination descriptions. Additionally, this program contributed to the formation of a village creative team to ensure the sustainability of digital tourism promotion. Overall, the program has proven effective in enhancing the competitiveness of tourism villages, empowering the local community, and maximizing the utilization of local potential